FORMATION OF AN INFORMED SOCIETY AND CRITERIA FOR ENSURING PUBLIC SAFETY (Scientific journal of the Fergana State University, 2024)
The article talks about the evolution of the concept of information, information society, its origins, and its essence. Also, this article analyzes the socio-philosophical and public security criteria related to the origin of the concept of information society.